2014
DOI: 10.1111/jsbm.12094
|View full text |Cite
|
Sign up to set email alerts
|

Does Founders' Human Capital Matter for Innovation? Evidence from Japanese Start-ups

Abstract: Using a sample from an original questionnaire survey in Japan, this paper explores whether and how founders' human capital affects innovation outcomes by start-ups.The results provide evidence that founders with greater human capital are more likely to yield innovation outcome. However, because certain types of founders' human capital may boost R&D investment, which possibly results in innovation outcomes, we estimate the determinants of innovation outcomes by an instrumental variable probit model taking into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 26 publications
2
71
2
4
Order By: Relevance
“…(Gupta et al, 2009) Some authors found out that, higher entrepreneurs' education can positively affect the performance of the firm and which also gives the company a more sustainable position in the market (Millian et al, 2014, Rauch andRijsdik 2013), can easily find the different sources of financing (Kato et al, 2015), and can manage better the firm-specific financial risks. (Wang, 2012).…”
Section: The Issue Of Small and Medium Enterprises Financing Is One Omentioning
confidence: 99%
“…(Gupta et al, 2009) Some authors found out that, higher entrepreneurs' education can positively affect the performance of the firm and which also gives the company a more sustainable position in the market (Millian et al, 2014, Rauch andRijsdik 2013), can easily find the different sources of financing (Kato et al, 2015), and can manage better the firm-specific financial risks. (Wang, 2012).…”
Section: The Issue Of Small and Medium Enterprises Financing Is One Omentioning
confidence: 99%
“…(Van der Sluis, and Van Praag, 2008) According to Kato, Okamuro, and Honjo (2015) a graduate entrepreneur can easily fi nd the diff erent sources of capital and by which he can invest in research and development that can increase the innovation of the small business from the specifi c market.…”
Section: Theoretical Partmentioning
confidence: 99%
“…Their findings revealed that prior work experience has important influences on the identification of market opportunities. Similarly, Kato, Okamuro, and Honjo () found that founders with greater human capital (generic and specific) are likely to achieve innovative outcomes.…”
Section: Theory and Hypothesesmentioning
confidence: 94%